A study on the non-law students perception towards law education acquisition / Jalilah Mohd Ali and Shamina Ali - Mohd Ali, Jalilah; Ali, Shamina (Research Management Institute (RMI), 2009)
Legal education at one point existed solely for those who wish to get themselves into the legal profession. Now matter has then got a little twist whereby law components are found in many other diploma and degree programmes. However, students from other disciplines have their much owned opinions towards law itself as being uninteresting and not related subject. Such negative experiences have been blamed for various reasons which are yet to determine on traditional ways of teaching law among tertiary education based students. Distribution of questionnaires in a small-scale research will be conducted to investigate students' perception of law and the challenges they faced in studying law. The discussion then proceeded to develop some of the themes arising from the questionnaires. The questions were the same for both undergraduate and postgraduate participants. The findings will award the merit in understanding the way students perceive in taking up law as a subject in terms of necessity or perhaps a requirement in their own disciplines hence guiding the educators to embark upon the obligatory actions